Assistance in Ecoprinting Batik Production for Partners Post-PPK Ormawa Activities Based on Ecological Literacy in Panggung Village, Tegal City - Mulyani, Sri (ASEAN Journal of Empowering Community, 2024)
This community service activity is a continuation of the previous activity, which was the creation of Ecoprinting batik, as part of the PPK Ormawa program. The sustainability of the Ecoprinting batik production process needs to be ensured, and this requires assistance. Community service activities in the form of assistance in Ecoprinting batik production based on Ecological Literacy, monitoring, and sustainability evaluation. Meetings with partners were held to identify the obstacles to the sustainability of batik production, provide materials on environmental sustainability, schedule batik production activities, assist in batik production based on ecological literacy, and develop a marketing plan for Ecoprinting batik. From the activity, the following data was obtained: the PKK Chairperson as the head of the ecoprinting batik artisans, the production schedule will include holidays, the location is in the tourist area of Pulau Kodok beach, and the material is environmental sustainability. Carried out in between batik production times. The marketing of Ecoprinting batik products is currently limited to the local community, entrusted to residents who own small shops or clothing stores. because the production is still not much, at the end of the service period, production is done if there are orders. Continuation of this program is necessary for the sustainability of production, including assistance in product creation and business analysis for participants who wish to become entrepreneurs, in order to improve family welfare.